Self-determined architecture: facilitating cultural futures and education with the First Nations Longhouse - Lommerse, Marina; Lommerse, J. (Common Ground Publishing, 2007)
The past 35 years have witnessed a cultural revival within Canada's aboriginal people and their relatives to the south. The growing number of native-determined buildings indicates the importance to aboriginal peoples to have buildings that house and reflect their current cultural concerns. Through this, a new native architecture has transpired. As described by Krinsky (1996, p. 10) "Modern Indian Architecture emerged in tandem with a movement to renew and enhance other aspects of Indian culture". However, exactly how the built environment plays a role in cultural rebuilding and communication is not always clear. To explore this question, this case study examines the First Nations Longhouse at the University of British Columbia (UBC), in Vancouver, Canada. The Longhouse was built with a conscious effort to articulate contemporary First Nations cultural identity. First Nations elders , UBC staff and students directed the project from beginning to end.Through the involvement of cross-tribal elders, historical memories (which are integral to the regeneration and redefinition of their culture) were communicated. Through the stories and ceremonies, designs and forms for the Longhouse emerged that could be used to symbolically represent the future. The First Nations Longhouse at UBC manifests the university's ambitious mission: "to encourage, welcome and support native people in higher education" (Owen, 1994, p. 200). It also stands as a symbol of opportunity for the native people of the Pacific Northwest. The First Nations community at UBC is in a transformational period. The community recognised this in the development of their Longhouse. The results of their work have created a hybrid. It is a transformative space where First Nations cultures and values can exist in the 21st century. The Longhouse is a significant example of the success of a self-determined approach to the creation of a culturally-sensitive building and space.